A retrospective review of acute liver failure in children admitted at Red Cross War Memorial Children's Hospital - Mlotha-Mitole, Rachel (Department of Paediatrics and Child Health, 2021)
Acute liver failure (ALF) describes a clinical syndrome resulting from severe liver damage and extensive loss of functional parenchymal liver mass triggered by various factors. Early recognition and initiation of specific therapy may improve outcomes and reduce the need for liver transplantation, a treatment modality not universally available in resource constraint areas. There is paucity of data describing this syndrome in Sub-Saharan Africa in children. Objective This study aims to retrospectively review and determine the clinical presentation, aetiology, complications & outcome of ALF in children admitted at the Red Cross War Memorial Children's Hospital (RCWMCH). Methods All records of children from 0 to 13 years admitted at the RCWMCH over the period from January 2005 to December 2016 with ALF were retrospectively reviewed, after obtaining ethical approval. Patients with pre-existing evidence of chronic liver disease were excluded. Demographic variables as well as clinical presentation and investigations were captured, with determination of outcomes at 3 weeks and 6 weeks of diagnosis. Results Study included 24 children., 16 females (66.7%) and 8 males (33.3%). Median Age was 15 months, with interquartile range from 5 to 28 months. Diarrhoea, jaundice, respiratory distress, hepatomegaly and encephalopathy were common clinical features. Aetiology was infection in 37.5 % of cases (n=9, 2 of whom had autoimmune hepatitis comorbidity) and hepatitis A was most common infectious cause (n=4, 44%). Causes were indeterminate in 29.2%. Two patients had autoimmune hepatitis without co-morbidity; Reye syndrome 12.5% and 17% had miscellaneous causes. Transaminases were raised to thousands in viral causes of hepatitis, with a low C reactive protein. INR >4 and Total Bilirubin>210umol/L were associated with death outcome (p=0.04 and p=0.03 respectively. Conclusion Viral hepatitis A is the leading infective cause of acute liver failure in this study cohort and 29.2% of cases were indeterminable. INR >4 and Bilirubin > 210umol/l were predictors of poor outcome. Follow up study is recommended to better understand clinical spectrum and outcomes of children with acute liver failure in this low resource setting.